Strategies for success: How learning approaches affect academic performance among university students. - Abdullah , Nurulannisa; Aziz, Nur Aznie; Mohd Shukry, Amira Idayu; Mat Nawi , Nur Ainatul Mardiah; Fadzil , Faizal Haini; Arshad , Izzatil Husna; Sain , Zohaib Hassan (Journal of Islamic, Social, Economics and Development, 2024)
Learning strategies are important for students at various levels of education. This means that a student's focus change while studying for continuous assessment than when learning to pass an exam. The objective of the study is to analyses the relationship between students’ academic performance and their learning strategies. A comprehensive analysis was conducted to investigate the impact of various learning strategies on students' academic achievement. The participants included a diverse sample of students from different educational levels and backgrounds. Data collection has been done through quantitative survey among university students at a renowned university in Malaysia, SPSS version 28 has been used to analyze the learning strategies and academic performance of students, which allowed for the examination of correlations and patterns in the data. The findings show a significant relationship between certain learning strategies and academic performance where students use the right strategies when studying will improve the students' academics. This study contributes to the understanding of the importance of learning strategies in optimizing students' academic success to improve the learning environment and promote better learning outcomes.